UN DIALOG CU IMPACT - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2020)
The article revels findings and impressions after a study tour supported by Novateca program at the National Library of Romania and “M. Sadoveanu” Metropolitan Library from București. Author describes new services that have been implemented by both libraries. Among them: The “Sound of pages”, “The third space of democracy”, Digital Library, Shelf of Initiatives and many more.